The analysis of pedagogic principles in the implementation of mathematics learning curriculum at islamic boarding schools - Andi Mawaddah Hamzah (Balai Diklat Keagamaan Ambon, 2022)
Islamic Boarding School, or Pesantren as the oldest educational institution in Indonesia, provides a unique attraction for research. The curriculum in Pesantren that integrates religious learning and general learning provides challenges for teachers in implementing learning. Although it has several advantages over public schools, Pesantren also has several problems. One of them is related to curriculum implementation. Therefore, this study aims to analyze the missing pedagogic principles in the application of the mathematics learning curriculum in Islamic boarding schools and also the impact of the loss of pedagogic principles. This research was in the form of qualitative research by interviewing four respondents, including the founder of the boarding school, the principal, the deputy headmaster of the curriculum section, and a math teacher at the Aliyah/Senior High School level. The findings of this study are: (1) the curriculum policy at Pesantren has not been understood collectively by education practitioners in the school, (2) The readiness in curriculum formulation is considered not optimal, and (3) The implementation of the curriculum 2013 in mathematics learning in Pesantren is not optimal due to other rules such as the determination of learning hours which are very lacking. This is accompanied by most pedagogical principles that should be present in learning, which cannot be implemented as a whole. The researcher recommends that there is a need for a unique curriculum formulated directly by mathematics teachers by adjusting existing materials and class hours so that educational goals can be achieved and implementing pedagogic principles in learning.